Lithium thionyl chloride battery electrolyte, preparation method thereof and lithium thionyl chloride battery

By introducing chlorinated polyvinyl chloride (CPVC) into the lithium subbattery electrolyte, a lithium chloride crystal passivation film with voids is formed, which solves the voltage hysteresis caused by long-term storage of lithium subbattery and improves the long-term storage load capacity of the battery.

CN119542448APending Publication Date: 2025-02-28HCB BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411916875.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Lithium sub-batteries are prone to voltage hysteresis problems after long-term storage, resulting in the inability to work normally.

Method used

Chlorinated polyvinyl chloride (CPVC) is introduced into the lithium sub-battery electrolyte to form an extremely thin CPVC cover layer. Over time, lithium chloride crystal passivation film is grown on it, forming a loose structure with voids and improving ion penetration.

Benefits of technology

It effectively improves the voltage hysteresis problem caused by long-term storage of lithium sub-batteries, improves the long-term storage load capacity of the battery, and reduces manufacturing difficulty and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542448A_ABST
    Figure CN119542448A_ABST
Patent Text Reader

Abstract

The invention provides a lithium thionyl chloride battery electrolyte, a preparation method thereof and a lithium thionyl chloride battery, the lithium thionyl chloride battery electrolyte comprises thionyl chloride, a lithium salt and an additive, and the additive comprises chlorinated polyvinyl chloride. The chlorinated polyvinyl chloride is introduced into the electrolyte of the lithium thionyl chloride battery, so that the voltage hysteresis phenomenon of the battery can be effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a lithium-ion battery electrolyte and a preparation method thereof and a lithium-ion battery. Background Art

[0002] Lithium-ion battery is a liquid lithium primary battery with thionyl chloride (SOCl2) as electrolyte solvent and positive electrode active material. It is the type with the highest specific energy and the widest operating temperature range among the current commercial battery products. At the same time, the characteristics of liquid batteries make its voltage stable for more than 90% of the time when the entire battery capacity is used. Nowadays, lithium-ion batteries are widely used in various types of smart meters such as electricity meters, water meters and gas meters, and are also being continuously applied and developed in the fields of transportation, security, Internet of Things, etc., which also puts higher requirements on the performance of lithium-ion batteries.

[0003] In lithium-ion batteries, although the positive active material tightly surrounds the lithium negative electrode, there is actually no short circuit phenomenon. This is because a layer of LiCl passivation film is formed on the surface of the negative electrode. Therefore, lithium-ion batteries have the advantages of low self-discharge rate and long storage life in the storage state. However, with the continuous growth of the LiCl passivation film, lithium-ion batteries will cause serious voltage hysteresis. That is, after long-term storage of lithium-ion batteries, serious voltage hysteresis will occur. When the voltage drops below the cut-off voltage required by instruments and meters, the instruments and meters will stop working. Therefore, how to reduce the hysteresis effect to ensure that the voltage of lithium-ion batteries can meet the requirements when used after long-term storage has become one of the research focuses.

[0004] After research, people have found ways to reduce the hysteresis effect, such as coating materials on the lithium surface to inhibit the growth of passivation film, but this method is difficult to manufacture and is not conducive to industrial production.

[0005] Therefore, there is an urgent need to provide a solution that is easy to manufacture and can solve the voltage hysteresis problem caused by long-term storage of lithium-ion batteries. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium-substrate battery electrolyte, a preparation method thereof, and a lithium-substrate battery. The present invention introduces chlorinated polyvinyl chloride (CPVC) into the lithium-substrate battery electrolyte, which quickly forms an extremely thin CPVC covering layer on the surface of the metal lithium negative electrode of the lithium-substrate battery. As the battery storage time increases, a lithium chloride crystal passivation film gradually grows thereon. CPVC will be doped into the lithium chloride crystal passivation film, and the morphology of the passivation film is no longer a regular crystal, but a loose structure with gaps. When the external circuit is connected, ions can pass through these doped gaps, thereby solving the voltage hysteresis problem caused by the long-term storage of the lithium-substrate battery. The preparation method of the lithium-substrate battery electrolyte is simple and has low difficulty.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a lithium-ion battery electrolyte, the lithium-ion battery electrolyte comprising thionyl chloride, a lithium salt and an additive, wherein the additive comprises chlorinated polyvinyl chloride.

[0009] The present invention introduces chlorinated polyvinyl chloride (CPVC) into the electrolyte of the lithium-ion battery, and quickly forms an extremely thin CPVC covering layer on the surface of the metal lithium negative electrode of the lithium-ion battery, and then gradually grows a lithium chloride crystal passivation film thereon as the battery storage time increases. When there is no CPVC covering layer, lithium chloride crystals will first grow sporadically on the lithium surface to form "islands". As time goes by, the "islands" gradually connect to form a dense lithium chloride crystal film, which is difficult for ions to penetrate, showing voltage hysteresis when the external circuit is connected. When there is a CPVC covering layer, CPVC will be doped into the subsequently grown lithium chloride crystal passivation film, and the morphology of the lithium chloride crystal passivation film is no longer a regular crystal, but a loose structure with gaps. When the external circuit is connected, ions can pass through these doped gaps, showing an improvement in the voltage hysteresis phenomenon of the battery, thereby improving the long-term storage load capacity of the lithium-ion battery.

[0010] Polyvinyl chloride (PVC) is a high molecular polymer that is almost insoluble. It is only slightly soluble in thionyl chloride, which is a strong organic halogenating agent. Compared with PVC, CPVC has a higher chlorine content, a smaller relative molecular mass, and a lower degree of polymerization, so it can be better dissolved in thionyl chloride. When the lithium-ion battery electrolyte containing CPVC is added to the battery, the balance of the halogenation is broken due to the effect of metallic lithium, the solubility is reduced, and CPVC will precipitate and adhere to the surface of the metallic lithium negative electrode to form an extremely thin covering layer.

[0011] In the present invention, chlorinated polyvinyl chloride (CPVC) has high stability in the electrolyte environment of lithium-ion battery, which has a positive impact on the long-term performance stability of the battery and the reduction of discharge capacity loss after high-temperature storage.

[0012] The preparation method of the lithium-ion battery electrolyte provided by the present invention is simple, low in difficulty, does not require the complicated operation of coating on the lithium surface, has low cost, and is conducive to industrial production.

[0013] Preferably, the mass content of chlorine in the chlorinated polyvinyl chloride is 65-68%, for example, it can be 65%, 66%, 67% or 68%, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the degree of polymerization of the chlorinated polyvinyl chloride is 500-700, for example, it can be 500, 520, 550, 580, 600, 620, 650, 680 or 700, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the content of heavy metal impurity ions in the chlorinated polyvinyl chloride is less than 30 ppm, for example, it can be 28 ppm, 25 ppm, 20 ppm, 10 ppm or 1 ppm, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the concentration of chlorinated polyvinyl chloride in the lithium-ion battery electrolyte is 0.005-0.02 g / L, for example, it can be 0.005 g / L, 0.008 g / L, 0.01 g / L, 0.012 g / L, 0.015 g / L, 0.018 g / L or 0.02 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the lithium salt comprises LiAlCl4.

[0018] Preferably, the concentration of lithium salt in the lithium-ion battery electrolyte is 0.6-1.8 mol / L, for example, it can be 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L or 1.8 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In a second aspect, the present invention provides a method for preparing the lithium-ion battery electrolyte according to the first aspect, the preparation method comprising:

[0020] (1) Prepare additive premix solution and lithium salt premix solution separately:

[0021] The chlorinated polyvinyl chloride powder is dissolved in thionyl chloride to obtain an additive premix solution.

[0022] The lithium salt is dissolved in thionyl chloride to obtain a lithium salt premix solution.

[0023] (2) Mixing the additive premix solution, the lithium salt premix solution and thionyl chloride to obtain the lithium-ion battery electrolyte.

[0024] It should be noted that the present invention does not limit the order of preparing the additive premix solution and preparing the lithium salt premix solution, and there is no particular order between the two.

[0025] In the present invention, chlorinated polyvinyl chloride (CPVC) powder and lithium salt are dissolved separately for the following reasons: the dissolution of lithium salt is not a fast and complete process. For example, LiAlCl4 is formed by melting AlCl3 and LiCl at high temperature. When dissolved in thionyl chloride, AlCl3 is dissolved first to form a Lewis acid, and then forms a complex with LiCl, so that LiCl is dissolved again. If CPVC is contained in thionyl chloride before the lithium salt is completely dissolved, CPVC will be doped and coated with LiCl, thereby affecting the dissolution of lithium salt. Even if the thionyl chloride in which the lithium salt is completely dissolved has very small LiCl freely dispersed in the thionyl chloride, it will also affect the dissolution of CPVC. The dissolution processes of the two affect each other, so they need to be dissolved separately.

[0026] The preparation method of the lithium-ion battery electrolyte provided by the invention is simple, easy to operate and is conducive to industrial production.

[0027] In the present invention, a relatively high concentration of additive premix solution can be prepared, and then an appropriate amount of the additive premix solution is mixed with a lithium salt premix solution and thionyl chloride to obtain a lithium-ion battery electrolyte having a target additive concentration and a target volume.

[0028] The additive premix prepared by the invention can be stored for a long time in a dry and sealed environment, and is convenient for industrial mass production.

[0029] Preferably, the bulk density of the chlorinated polyvinyl chloride powder is 0.44-0.45 g / mL, for example, it can be 0.44 g / mL, 0.442 g / mL, 0.444 g / mL, 0.446 g / mL, 0.448 g / mL or 0.45 g / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the particle size of the chlorinated polyvinyl chloride powder is ≤400 μm, for example, it can be 400 μm, 350 μm, 300 μm, 250 μm, 200 μm, 100 μm, 50 μm or 10 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the concentration of chlorinated polyvinyl chloride in the additive premix is ​​0.2-0.5 g / L, for example, it can be 0.2 g / L, 0.25 g / L, 0.3 g / L, 0.35 g / L, 0.4 g / L, 0.45 g / L or 0.5 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In the present invention, when the additive premix solution of the above preferred concentration is mixed with the lithium salt premix solution and thionyl chloride, the specific amount of the additive premix solution is related to the target volume and target additive concentration of the lithium-ion battery electrolyte.

[0033] Preferably, the specific steps of dissolving in step (1) include: mixing chlorinated polyvinyl chloride powder and thionyl chloride, and performing condensation reflux heating.

[0034] Preferably, the heating rate of the condensation reflux heating is 0.5-2°C / min, for example, it can be 0.5°C / min, 0.8°C / min, 1°C / min, 1.5°C / min or 2°C / min, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the insulation temperature of the condensation reflux heating is 72-78°C, for example, it can be 72°C, 73°C, 74°C, 75°C, 76°C, 77°C or 78°C, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the insulation time of the condensation reflux heating is ≥ 2h, for example, it can be 2h, 4h, 6h, 8h, 10h, 15h, 20h or 24h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the condensation reflux heating process is accompanied by stirring, and the stirring rate is 200-300r / min, for example, it can be 200r / min, 220r / min, 240r / min, 260r / min, 280r / min or 300r / min, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the condensing medium used in the condensation reflux heating includes silicone oil.

[0039] Preferably, the temperature of the condensing medium used in the condensation reflux heating is 15-25°C, for example, it can be 15°C, 16°C, 17°C, 18°C, 20°C, 22°C or 25°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the ratio of the volume of thionyl chloride required for preparing the lithium salt premix to the target volume of the lithium-sulfur battery electrolyte is 0.6-0.7, for example, it can be 0.6, 0.62, 0.64, 0.66, 0.68 or 0.7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, in step (2), after the mixing, a step of introducing sulfur dioxide gas is further performed.

[0042] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:

[0043] (I) adding chlorinated polyvinyl chloride powder to thionyl chloride at a temperature of 22-28°C and a relative humidity of less than 1%, performing condensation reflux heating to completely dissolve the chlorinated polyvinyl chloride powder, and then naturally cooling to room temperature to obtain an additive premix; wherein the mass content of chlorine element in the chlorinated polyvinyl chloride powder is 65-68%, and the content of heavy metal impurity ions is less than 30ppm; the polymerization degree of the chlorinated polyvinyl chloride powder is 500-700, the bulk density is 0.44-0.45g / mL, and the particle size is ≤400μm; the heating rate of the condensation reflux heating is 0.5-2°C / min, the insulation temperature is 72-78°C, and the insulation time is ≥2h; the condensation reflux heating process is accompanied by stirring, and the stirring rate is 200-300r / min; the condensation medium used in the condensation reflux heating is 15-25°C silicone oil; the concentration of chlorinated polyvinyl chloride in the additive premix is ​​0.2-0.5g / L.

[0044] (II) dissolving a lithium salt in thionyl chloride, and then refluxing to remove impurities. After the reflux and impurity removal is completed, the temperature is lowered to room temperature to obtain a lithium salt premix solution; wherein the lithium salt is LiAlCl4.

[0045] (III) adding part of the additive premix to the lithium salt premix, stirring evenly, then adding thionyl chloride, mixing evenly and fixing the volume to the target volume, and then introducing sulfur dioxide gas to obtain the lithium-ion battery electrolyte; wherein the ratio of the volume of thionyl chloride in step (II) to the target volume in step (III) is 0.6-0.7; and the concentration of chlorinated polyvinyl chloride in the lithium-ion battery electrolyte is 0.005-0.02 g / L.

[0046] In the present invention, the room temperature is 25±3°C.

[0047] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium-ion battery electrolyte described in the first aspect, or the lithium-ion battery electrolyte prepared by the preparation method described in the second aspect.

[0048] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] The present invention introduces chlorinated polyvinyl chloride (CPVC) into the electrolyte of the lithium-ion battery, and quickly forms an extremely thin CPVC covering layer on the surface of the metal lithium negative electrode of the lithium-ion battery, and then gradually grows a lithium chloride crystal passivation film thereon as the battery storage time increases. When there is no CPVC covering layer, lithium chloride crystals will first grow sporadically on the lithium surface to form "islands". As time goes by, the "islands" gradually connect to form a dense lithium chloride crystal film, which is difficult for ions to penetrate, showing voltage hysteresis when the external circuit is connected. When there is a CPVC covering layer, CPVC will be doped into the subsequently grown lithium chloride crystal passivation film, and the morphology of the lithium chloride crystal passivation film is no longer a regular crystal, but a loose structure with gaps. When the external circuit is connected, ions can pass through these doped gaps, showing an improvement in the voltage hysteresis phenomenon of the battery, thereby improving the long-term storage load capacity of the lithium-ion battery.

[0051] In the present invention, chlorinated polyvinyl chloride (CPVC) has high stability in the electrolyte environment of lithium-ion battery, which has a positive impact on the long-term performance stability of the battery and the reduction of discharge capacity loss after high-temperature storage.

[0052] The preparation method of the lithium-ion battery electrolyte provided by the present invention is simple, low in difficulty, does not require the complicated operation of coating on the lithium surface, has low cost, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 A schematic diagram of a process for preparing a lithium-ion battery electrolyte according to an embodiment of the present invention.

[0054] Figure 2 The voltage hysteresis test curve diagram of the lithium-ion battery corresponding to Example 1 of the present invention and Comparative Example 1 after long-term high-temperature storage.

[0055] Figure 3 The discharge capacity test curves of the lithium-ion battery corresponding to Example 1 and Comparative Example 1 of the present invention after long-term high-temperature storage are shown. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0057] In one embodiment, the present invention provides a method for preparing a lithium-ion battery electrolyte, the process of which is as follows: Figure 1 As shown, the following steps are included:

[0058] (1) Mix chlorinated polyvinyl chloride and thionyl chloride and keep stirring, perform condensation reflux heating until the chlorinated polyvinyl chloride is completely dissolved, cool naturally to obtain an additive premix solution, and seal and store.

[0059] (2) Dissolve the lithium salt in thionyl chloride to obtain a lithium salt premix solution.

[0060] (3) Add the additive premix to the lithium salt premix, mix well, add pure thionyl chloride, mix well, adjust the volume to the target volume required for the lithium-ion battery electrolyte, and then introduce sulfur dioxide to obtain the lithium-ion battery electrolyte. The obtained lithium-ion battery electrolyte can be directly injected into the battery.

[0061] Example 1

[0062] This embodiment provides a method for preparing a lithium-ion battery electrolyte, comprising the following steps:

[0063] (1) Under the condition of temperature of 25±3°C and relative humidity of less than 1%, 2L of thionyl chloride is weighed and added into a single-necked flask, and then 0.5g of chlorinated polyvinyl chloride powder is added thereto; the flask is connected to a serpentine condenser, the condensing medium introduced into the serpentine condenser is 15°C silicone oil, and condensation reflux heating is performed under the condition of a magnetic stirring rate of 300r / min: the temperature is slowly raised to 75±1°C at a rate of 2°C / min, and the temperature is kept for 3h to completely dissolve the chlorinated polyvinyl chloride powder, and then naturally cooled to room temperature to obtain an additive premix solution, which is sealed and stored; wherein the mass content of chlorine element in the chlorinated polyvinyl chloride powder is 65%, and the content of heavy metal impurity ions is less than 30ppm; the degree of polymerization of the chlorinated polyvinyl chloride powder is 600, the bulk density is 0.44g / mL, and the particle size is ≤400μm; the concentration of chlorinated polyvinyl chloride in the additive premix solution is 0.25g / L.

[0064] (2) Take another flask, weigh 2 L of thionyl chloride and add it into a single-necked flask, then add 634 g of LiAlCl4, and reflux to remove impurities. After the reflux and impurity removal is completed, wait for the temperature to drop to room temperature to obtain a lithium salt premix solution.

[0065] (3) 0.12 L of the additive premix was taken and added to the lithium salt premix, and the mixture was stirred evenly. Then, pure thionyl chloride was added, the mixture was mixed evenly, and the volume was fixed to 3 L. Subsequently, 230 g of sulfur dioxide gas was introduced to obtain a lithium-thionyl battery electrolyte.

[0066] In the lithium-ion battery electrolyte prepared in this embodiment, the concentration of chlorinated polyvinyl chloride is 0.01 g / L.

[0067] Example 2

[0068] The difference between this embodiment and embodiment 1 is that the volume of the additive premix in step (3) is adjusted so that the concentration of chlorinated polyvinyl chloride in the lithium-ion battery electrolyte is adjusted to 0.003 g / L.

[0069] The remaining parameters remain the same as those in Example 1.

[0070] Example 3

[0071] The difference between this embodiment and embodiment 1 is that the volume of the additive premix in step (3) is adjusted so that the concentration of chlorinated polyvinyl chloride in the lithium-ion battery electrolyte is adjusted to 0.025 g / L.

[0072] The remaining parameters remain the same as those in Example 1.

[0073] It can be seen from Example 1 and Examples 2-3 that in the lithium-ion battery electrolyte, if the concentration of chlorinated polyvinyl chloride is too low, the improvement effect of voltage hysteresis is not obvious; if the concentration of chlorinated polyvinyl chloride is too high, the initial ohmic internal resistance of the battery is too high, and the load voltage of the battery will be reduced throughout its life cycle.

[0074] Example 4

[0075] The difference between this embodiment and embodiment 1 is that the mass content of chlorine element in the chlorinated polyvinyl chloride powder is 60%.

[0076] The remaining parameters remain the same as those in Example 1.

[0077] It can be seen from Examples 1 and 4 that, in the chlorinated polyvinyl chloride powder, if the mass content of chlorine is too low, it is difficult to dissolve the CPVC and an ideal additive premix cannot be prepared; and the upper limit of the chlorine content is mainly affected by the preparation process of the CPVC product. The upper limit of the chlorine content of the CPVC products that can be stably provided on the market is about 68%.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that chlorinated polyvinyl chloride is not added.

[0080] The remaining parameters remain the same as those in Example 1.

[0081] Performance Testing

[0082] The electrolytes provided in Example 1 and Comparative Example 1 were subjected to the following tests:

[0083] (1) Voltage hysteresis test:

[0084] The prepared lithium-substrate battery electrolyte is injected into an ER14250 battery, wherein the electrodes are a lithium metal electrode and a carbon electrode, and the diaphragm is a glass fiber diaphragm. After the injection is completed, an ER14250 lithium-substrate battery is obtained.

[0085] The ER14250 lithium-ion battery was stored at 60°C for 30 days. After the battery was taken out, the load voltage under 330Ω was tested at 25±3°C for 3s, and a data was recorded every 0.001s.

[0086] (2) Discharge capacity test:

[0087] The prepared lithium-substrate battery electrolyte is injected into an ER14250T battery, wherein the electrodes are a lithium metal electrode and a carbon electrode, and the diaphragm is a glass fiber diaphragm. After the injection is completed, an ER14250T lithium-substrate battery is obtained.

[0088] The ER14250T lithium-ion battery was stored at 70°C for 30 days. After the battery was taken out, it was discharged at a constant current of 2mA at a temperature of 23°C with a cut-off voltage of 2V.

[0089] The test results are as follows Figure 2 and Figure 3 shown.

[0090] Figure 2 The figure shows the comparison of the voltage hysteresis of the lithium-ion battery corresponding to Example 1 and Comparative Example 1 after long-term high-temperature storage. It can be seen from the figure that the initial transient load voltage (TMV) of Example 1 after high-temperature storage is 3.409V, which is significantly higher than 3.156V of Comparative Example 1. The 3s end-load voltage (CCV) of Example 1 after high-temperature storage is 3.523, which is significantly higher than 3.451 of Comparative Example 1. This shows that the introduction of chlorinated polyvinyl chloride into the electrolyte of the present invention can effectively improve the voltage hysteresis caused by long-term storage of lithium-ion batteries.

[0091] Figure 3 The figure shows a comparison of the discharge capacities of the lithium-ion battery after long-term high-temperature storage corresponding to Example 1 and Comparative Example 1. It can be seen from the figure that the capacity of Example 1 after high-temperature storage is 1009 mAh, which is significantly higher than the 932 mAh of Comparative Example 1. This shows that the use of the electrolyte of the present invention can significantly improve the discharge capacity of the lithium-ion battery after long-term storage.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 1 is that chlorinated polyvinyl chloride is replaced by polyvinyl chloride.

[0094] The remaining parameters remain the same as those in Example 1.

[0095] It can be seen from Example 1 and Comparative Example 2 that, compared with polyvinyl chloride, chlorinated polyvinyl chloride has a higher solubility in thionyl chloride and can be used to prepare an additive premix, while polyvinyl chloride can only be added to a prepared electrolyte and will result in uneven dissolution of lithium salts or additives.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 1 is that step (2) is omitted, and the step (1) of "weighing 2 L of thionyl chloride and adding it into a single-necked flask, and then adding 0.5 g of chlorinated polyvinyl chloride powder thereto" is adjusted to "weighing 0.03 g of chlorinated polyvinyl chloride powder and 634 g of LiAlCl4 and mixing them uniformly to obtain a mixed material, and then weighing 2.12 L of thionyl chloride and adding it into a single-necked flask, and then adding the mixed material into the flask".

[0098] The remaining parameters remain the same as those in Example 1.

[0099] It can be seen from Example 1 and Comparative Example 3 that when preparing a lithium-ion battery electrolyte, if the chlorinated polyvinyl chloride powder and the lithium salt are first mixed and then dissolved in thionyl chloride, small milky white suspended particles visible to the naked eye will be produced, and the solution preparation effect is not good.

[0100] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium-ion battery electrolyte, characterized in that: The lithium-ion battery electrolyte includes thionyl chloride, lithium salt and additives, and the additives include chlorinated polyvinyl chloride.

2. The lithium-ion battery electrolyte according to claim 1, characterized in that: The mass content of chlorine in the chlorinated polyvinyl chloride is 65-68%; Preferably, the degree of polymerization of the chlorinated polyvinyl chloride is 500-700; Preferably, the content of heavy metal impurity ions in the chlorinated polyvinyl chloride is less than 30 ppm; Preferably, the concentration of chlorinated polyvinyl chloride in the lithium-ion battery electrolyte is 0.005-0.02 g / L.

3. The lithium-ion battery electrolyte according to claim 1 or 2, characterized in that: The lithium salt includes LiAlCl4.

4. A method for preparing a lithium-ion battery electrolyte according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) Prepare additive premix solution and lithium salt premix solution separately: dissolving chlorinated polyvinyl chloride powder in thionyl chloride to obtain an additive premix solution; dissolving a lithium salt in thionyl chloride to obtain a lithium salt premix solution; (2) Mixing the additive premix solution, the lithium salt premix solution and thionyl chloride to obtain the lithium-ion battery electrolyte.

5. The preparation method according to claim 4, characterized in that: The bulk density of the chlorinated polyvinyl chloride powder is 0.44-0.45 g / mL; Preferably, the particle size of the chlorinated polyvinyl chloride powder is ≤400 μm; Preferably, the concentration of chlorinated polyvinyl chloride in the additive premix is ​​0.2-0.5 g / L.

6. The preparation method according to claim 4 or 5, characterized in that: The specific steps of dissolving in step (1) include: mixing chlorinated polyvinyl chloride powder and thionyl chloride, and performing condensation reflux heating; Preferably, the heating rate of the condensation reflux heating is 0.5-2°C / min; Preferably, the insulation temperature of the condensation reflux heating is 72-78°C; Preferably, the insulation time of the condensation reflux heating is ≥ 2h.

7. The preparation method according to claim 6, characterized in that: The condensation reflux heating process is accompanied by stirring, and the stirring rate is 200-300r / min; Preferably, the condensing medium used in the condensation reflux heating includes silicone oil; Preferably, the temperature of the condensing medium used in the condensation reflux heating is 15-25°C.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The ratio of the volume of thionyl chloride required for preparing the lithium salt premix to the target volume of the lithium-ion battery electrolyte is 0.6-0.7; Preferably, in step (2), after the mixing, a step of introducing sulfur dioxide gas is further performed.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method specifically comprises the following steps: (I) adding chlorinated polyvinyl chloride powder to thionyl chloride at a temperature of 22-28° C. and a relative humidity of less than 1%, performing condensation reflux heating to completely dissolve the chlorinated polyvinyl chloride powder, and then naturally cooling to room temperature to obtain an additive premix solution; The mass content of chlorine in the chlorinated polyvinyl chloride powder is 65-68%, and the content of heavy metal impurity ions is less than 30ppm; the degree of polymerization of the chlorinated polyvinyl chloride powder is 500-700, the bulk density is 0.44-0.45g / mL, and the particle size is ≤400μm; the heating rate of the condensation reflux heating is 0.5-2℃ / min, the insulation temperature is 72-78℃, and the insulation time is ≥2h; the condensation reflux heating process is accompanied by stirring, and the stirring rate is 200-300r / min; the condensation medium used in the condensation reflux heating is 15-25℃ silicone oil; the concentration of chlorinated polyvinyl chloride in the additive premix is ​​0.2-0.5g / L; (II) dissolving the lithium salt in thionyl chloride, and then refluxing to remove impurities, and after the reflux and impurity removal is completed, the temperature is lowered to room temperature to obtain a lithium salt premix solution; Wherein, the lithium salt is LiAlCl4; (III) adding a portion of the additive premix to the lithium salt premix, stirring evenly, then adding thionyl chloride, mixing evenly and fixing the volume to the target volume, and then introducing sulfur dioxide gas to obtain the lithium-sulfur battery electrolyte; Wherein, the ratio of the volume of thionyl chloride in step (II) to the target volume in step (III) is 0.6-0.7; and the concentration of chlorinated polyvinyl chloride in the lithium-ion battery electrolyte is 0.005-0.02 g / L.

10. A lithium-ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery electrolyte described in any one of claims 1 to 3, or the lithium-ion battery electrolyte prepared by the preparation method described in any one of claims 4 to 9.